2021
DOI: 10.1016/j.amsu.2021.102450
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with dengue prevention behaviour in riverbank area: A cross-sectional study

Abstract: Introduction Dengue has been a burden, especially in tropical country. Indonesian Ministry of Health promote dengue prevention through environmental control with 3 M (covering water storage, cleaning water storage, and recycling unused items) practices. Here we analyzed factors associated with dengue prevention behavior in riverbank area of Yogyakarta Province. Methods The study employed cross-sectional survey covering riverbank area of Sendowo, Yogyakarta Province. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
1
5
1
Order By: Relevance
“…This study is consistent with previous studies, which stated that there was no relationship between the behavior of reusing or recycling used goods and the presence of Aedes aegypti mosquito larvae [22]. Another study stated that the behavior of 3M plus, mainly recycling used goods was not a risk factor for the incidence of DHF [14].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This study is consistent with previous studies, which stated that there was no relationship between the behavior of reusing or recycling used goods and the presence of Aedes aegypti mosquito larvae [22]. Another study stated that the behavior of 3M plus, mainly recycling used goods was not a risk factor for the incidence of DHF [14].…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, the city of Bandung is an administrative area, so used goods or plastic waste will be transported by cleaners regularly. In society, especially in urban areas, used goods will usually be transported by cleaners so the behavior of recycling used goods tends to be low so that behavior will be difficult to measure [14]. This study did not analyze people's habits in disposing of waste in its place.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research did not find a link between income level and dengue prevention behaviour. In contrast to the results of research in Malaysia on 2,512 respondents aged 18-60 years, respondents who have low incomes are associated with low dengue prevention practices [10], [12]. Another study also found something similar where high socioeconomic groups showed better prevention practices [13].…”
Section: Resultsmentioning
confidence: 83%
“…Previous research has revealed many factors that influence the practice of preventing dengue fever, including studies in Malaysia and Indonesia which show low income, low education, low knowledge and even age and gender are associated with low levels of dengue fever prevention [8], [9]. However, several other studies reveal that education does not have an essential role in preventive behaviour [10], [11]. Good prevention practices in the community are needed to prevent or minimise dengue fever cases successfully.…”
Section: Introductionmentioning
confidence: 99%